PKM Meningkatkan Kemampuan Menulis Artikel Ilmiah Guru di Kabupaten Enrekang - Arsad Bahri; Sultan Sultan; Yogi Saputra; Hardianto Hardianto; Muh. Arifuddin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The role of the teacher in advancing education and in preparing quality human resources is very important and strategic. Based on this important role, qualified teachers in the present and in the future are absolutely necessary. One of the efforts to develop sustainable professionalism includes sub-elements of personal development, scientific publications, and innovative work. Scientific publications can include publications on research results or innovative ideas in the field of formal education and textbook. In fact, teachers in Enrekang Regency still have problems in writing scientific articles both due to external and internal factors. This community partnership program is a solution to the teacher's problems through the training in the form of material delivery, practical work, discussions, questions and answers, the provision of independent/structured assignments, task reviews, and direct and online consultation. After the training activities are finished, participants give a positive response to the training both in terms of increasing knowledge, the relevance of the activity to the needs, and participant satisfaction with the implementation of the activity.